The Effect of Mergers and Acquisitions on Firm’s Performance: Evidence from the High-tech Industry in the US Market - Peng, Lin (2014)
In the finance literature, there is an important stream which examines the stock market reactions to merger and acquisition (M&A) activities, in both the short run and long run. Although most evidence indicates significantly positive post-merger returns to targets, the empirical researches fail to reach a consistent conclusion for acquirers. This paper tries to examine the stock market abnormal performance of the acquiring firms around the merger announcement date in the short run by focusing on the U.S. stock market. In addition, this paper specifically looks at the mergers and acquisitions in the high-tech industries, in order to determine whether the research is sensitive to the choice of industry sectors. The research sample includes 60 merger and acquisition deals within the high-tech industries in the U.S. market during the period from 2000 to 2005. Event study methodology is adopted to investigate the stock market abnormal performance of the acquiring firms. OLS multiple-regression is also used to examine the effect of some critical factors. The results of two tailed T-test show that the abnormal returns of the acquiring firms are all statistically significantly negative around the merger announcement date. This finding implies that the market overall makes negative reactions to mergers within the U.S. high-tech industries in the short run. Besides, the regression analysis show a slightly negative effect of acquiring firm size and a strong negative effect of target relative size to acquirer on the acquirer’s abnormal return in the U.S. high-tech industries in the short run. The examination of the effect of payment method suggests that mergers with cash payment outperform mergers with stock payment. Besides, certain significantly positive relationship is found between Tobin’s Q of the target firm and acquirers’ abnormal returns. It implies that, in the U.S. high-tech industries, bidders can create more value from taking over firms with better performance. Keywords: M&A, High-tech industry, Event study.